If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -2 + -5k Solving 3 = -2 + -5k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '5k' to each side of the equation. 3 + 5k = -2 + -5k + 5k Combine like terms: -5k + 5k = 0 3 + 5k = -2 + 0 3 + 5k = -2 Add '-3' to each side of the equation. 3 + -3 + 5k = -2 + -3 Combine like terms: 3 + -3 = 0 0 + 5k = -2 + -3 5k = -2 + -3 Combine like terms: -2 + -3 = -5 5k = -5 Divide each side by '5'. k = -1 Simplifying k = -1
| 1+7(3p+4)=15+7p | | 5-3z-18=z-1+8x | | 6(3x-5)-2(-6x+4)= | | -(-2x-8y-3)= | | 4x+9=x+4+8x | | 2x-3x=12 | | 2(9y-10)=40 | | -2y-10=5y+10 | | 3+-4a=11 | | 3x+3-x=2+x+2 | | 29+5n=-4(-6n-6)+5 | | -17-5n=8n-2(4+5n) | | 4(x+12)+5=9x-48 | | 12n+3=39 | | 2x^3+8=24 | | -2(x+4)=-3x+8 | | -31+18x-17X+9= | | 3(2r+5)-4(r-9)= | | -2(1+x)=7-5x | | b-4=-19 | | -7(-6b-5)=35-5b | | 6(2x-10)=0 | | 14+3d-7=12.10 | | -5(x+6)=5x-20 | | -(8+x)=-8+7x | | -18=18v | | 14x^2+10x-8=0 | | 2(t-4)-3(4t-5)=10-5(7t+3) | | 32+4m=-3(-5m-2)+2m | | -3(n-5)=15+4n | | 6x-2=3x-10 | | 4(1/4+x)=5 |